Insights into Asymmetric Liposomes as a Potential Intervention for Drug Delivery Including Pulmonary Nanotherapeutics - Yaqeen Nadheer Al Badri; Cheng Shu Chaw; Amal Ali Elkordy (MDPI AG, 2023)
Liposome-based drug delivery systems are nanosized spherical lipid bilayer carriers that can encapsulate a broad range of small drug molecules (hydrophilic and hydrophobic drugs) and large drug molecules (peptides, proteins, and nucleic acids). They have unique characteristics, such as a self-assembling bilayer vesicular structure. There are several FDA-approved liposomal-based medicines for treatment of cancer, bacterial, and viral infections. Most of the FDA-approved liposomal-based therapies are in the form of conventional "symmetric" liposomes and they are administered mainly by injection. Arikace® is the first and only FDA-approved liposomal-based inhalable therapy (amikacin liposome inhalation suspension) to treat only adults with difficult-to-treat Mycobacterium avium complex (MAC) lung disease as a combinational antibacterial treatment. To date, no "asymmetric liposomes" are yet to be approved, although asymmetric liposomes have many advantages due to the asymmetric distribution of lipids through the liposome's membrane (which is similar to the biological membranes). There are many challenges for the formulation and stability of asymmetric liposomes. This review will focus on asymmetric liposomes in contrast to conventional liposomes as a potential clinical intervention drug delivery system as well as the formulation techniques available for symmetric and asymmetric liposomes. The review aims to renew the research in liposomal nanovesicle delivery systems with particular emphasis on asymmetric liposomes as future potential carriers for enhancing drug delivery including pulmonary nanotherapeutics.